1987
DOI: 10.1182/blood.v70.2.456.bloodjournal702456
|View full text |Cite
|
Sign up to set email alerts
|

The protooncogene c-fos is transcriptionally active in normal human granulocytes

Abstract: Total cellular RNA of highly purified normal human blood cell populations was analyzed for the expression of the protooncogene c-fos, the cellular counterpart of the transforming FBJ virus. In marked contrast to previous findings based on in vitro studies with permanent leukemic cell lines, c-fos transcription was restricted to granulocytes. Neither blood monocytes nor blood lymphocytes or alveolar macrophages revealed detectable levels of c-fos transcription. Whereas this cellular oncogene is constitutively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…A minor band of about 3.4 kb, suggested to be a precursor molecule [1,2], was also evident, but only after overexposure of the autoradiogram. The sizes of jun B and jun D transcripts were about 2.1 and 2.0 kb respectively, as already reported [10,21]. The level of expression found for c-jun mRNA was comparable with that found for the 2.2 kb c-fos mRNA ([9]; F. Mollinedo & J. R. Naranjo, unpublished work).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…A minor band of about 3.4 kb, suggested to be a precursor molecule [1,2], was also evident, but only after overexposure of the autoradiogram. The sizes of jun B and jun D transcripts were about 2.1 and 2.0 kb respectively, as already reported [10,21]. The level of expression found for c-jun mRNA was comparable with that found for the 2.2 kb c-fos mRNA ([9]; F. Mollinedo & J. R. Naranjo, unpublished work).…”
Section: Resultssupporting
confidence: 85%
“…Two other c-jun-related cDNAs have been isolated (jun B and jun D), whose encoded proteins show extensive amino acid sequence identity with c-Jun/AP-and are able to form nuclear complexes with c-Fos or Fos-related proteins [7,8]. It has been found that human granulocytes express constitutively high levels of c-fos mRNA [9][10][11][12], which were increased upon cell activation by distinct stimuli [9][10][11][12][13]. Thus it was of importance to examine the expression of the jun family genes in granulocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Given the evidence that sgk is an immediate-early gene, its time-course of expression was compared to c-fos, another immediate-early gene known to be up-regulated by GM-CSF in granulocytes. Freshly isolated human peripheral blood granulocytes contain appreciable levels of c-fos mRNA [17,60,61]. Various stimulators of granulocyte function, including GM-CSF, can further increase c-fos levels [17,62].…”
Section: Resultsmentioning
confidence: 99%
“…In PMN performing 'frustrated' phagocytosis we did not find significant differences in the NF-κB pathway, however, FOS and JUN (the proteins c-fos and c-jun form the transcriptional regulator AP-1) were both increasingly expressed. PMN have been reported to constitutively express family members of FOS and JUN on transcriptional as well as c-fos and c-jun on translational level [32][33][34][35] with the steady state level of their RNA transcripts being rapidly up-regulated in response to several stimuli [36,37]. However, neither the proteins c-jun and c-fos nor the protein AP-1 has been shown to be up-regulated in PMN after exposure to diverse stimuli as indicated by our results and as reported by others [34,35].…”
Section: Discussionmentioning
confidence: 99%